The Linguistic Sensitivity of Lorenzo Campano in His Scientific and Technical Production - Corveddu, Mario Salvatore (2021)
The present study focuses on the figure of Lorenzo Campano, a prolific nineteenth-century author of whom we know nothing outside of his work composed of books of various kinds, among which stand out pedagogical works, stories, scientific-technical manuals, and a dictionary. We will focus on his specialized work, a manual on leather tanning and dressing and another on beer production, with the aim of analyzing the author's linguistic awareness and his perception of lexical dynamics. Throughout the study, we have analyzed the paratext and the annotations with which Campano enriches his works, and we found traces not only of his sensitivity to linguistic data, but of sensitivity to the processes of lexical change due to the diatechnic development of the nineteenth century. The nature and contents of Campano's annotations on the one hand make it clear that his linguistic awareness influenced his production, on the other hand they document some of the processes of the unprecedented change that the lexicon was undergoing.